Metropolitan area network re-architecture - Huanan CHEN; Xia GONG; Yongqing ZHU; Youming WU; Cancan HUANG (Dianxin kexue)
Digitization and intelligentization have become the main goals of infrastructure construction.As the most important part of the evolution of the network,the re-architecture of metropolitan area network (MAN) has directly determined the advanced level of the operator’s network.According to the new requirements,detail evolution of MAN re-architecture was discussed in detail based on the development of the key technologies and its application scene.Finally,the phased evolution solution was proposed,which can provide guidance for the technology research and the evolution of network re-architecture.